Laser Techniques and Laser Physics in Polish Laboratories - Abramski, Krzysztof (Photonics Letters of Poland, 2013)
<!--[if gte mso 9]> Normal 0 21 false false false PL X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]--><span style="font-size: 8.0pt; font-family: ";Times New Roman";,";serif";; mso-fareast-font-family: ";Times New Roman";; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-US">The major part of the current issue of Photonics Letters of Poland and its full next edition are devoted to Lasers ? their Physics and Technologies developed in Polish laboratories. There are a few groups in Poland working on different kind of lasers. The aim of these two editions is to show their current results, advances and prospective. This issue contains 7 papers dealing mainly with quantum cascade lasers, semiconductor lasers and solid state and fiber lasers.<!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <![endif]-->